Um mito moderno sobre coisas vistas nas HQs: explorando mitos e símbolos nas eras dos super-heróis - Vieira, Jordan Eliakin da Silva (2023)
This research investigates the presence of symbolic aspects and archetypal images in the ages of superheroes comic books (comics). The research uses theoretical foundations based on Analytical Psychology and Campbell's mythological propositions and we consider comics as a contemporary form of mythology. Through a bibliographic review we used the Junguian Arts Based Research, by Susan Rowland, which allows the full application of Jungian methods of symbolic interpretation, the work analyzes comic book characters and narratives, seeking to understand the presence of symbolic images in the various eras of superhero comics. The results reveal the consonance between the presence of symbolic elements in the ages of superhero comics, which can be understood from their mythological aspect, highlighting the relevance of comics as a very fruitful object of study and capable of contributing to the field of knowledge of Analytical Psychology